Stem cell extracellular vesicles: a new dawn for anti-inflammatory treatment of neurodegenerative diseases - Yu, Miao; Ma, Hongxia; Lai, Xiaoyi; Wu, Jiannan; Shen, Mengmeng; Yan, Junqiang (Frontiers in Aging Neuroscience, 2025)
Mesenchymal stem cell-derived extracellular vesicles, as carriers for intercellular communication, are rich in bioactive substances such as proteins and nucleic acids, and show unique potential in the treatment of neurodegenerative diseases. Their vesicular structure, with a diameter of 30–150 nm, can penetrate the blood–brain barrier and modulate the activity of microglia and astrocytes by delivering functional molecules. This process inhibits the release of pro-inflammatory factors and enhances the expression of anti-inflammatory mediators, thereby alleviating neuroinflammation in the pathological process of neurodegenerative diseases. As natural drug carriers, extracellular vesicles can improve the targeted delivery efficiency of therapeutic molecules. However, their specific anti-inflammatory mechanisms remain not fully understood and require further exploration. This article discusses the anti-inflammatory effects in the context of neurodegenerative diseases and provides a summary and outlook on the anti-inflammatory actions associated with extracellular vesicles from past research.